Surface plasmon resonance biosensor for direct detection of antibody against Epstein-Barr virus - Vaisocherová, Hana; Mrkvová, Kateřina; Piliarik, Marek; Jinoch, Pavel; Šteinbachová, Marie; Homola, Jiří (Biosensors & bioelectronics, 2007)
This paper describes the direct label-free detection of antibodies against the Epstein-Barr virus (anti-EBNA) using a surface plasmon resonance (SPR) biosensor. The antibody detection was performed using the immunoreaction between anti-EBNA and a respective synthetic peptide (EBNA-1), which was conjugated with bovine serum albumin (BSA-EBNA) and immobilized on the sensor surface. Three immobilization chemistries for the attachment of BSA-EBNA were investigated to optimize ligand density and minimize loss of EBNA-1 immunoreactivity. The developed SPR biosensor functionalized with the optimal immobilization method was calibrated and characterized in terms of detection limit, reproducibility, regenerability and storability. It was demonstrated that the sensor is capable of detecting concentrations of anti-EBNA as low as 0.2 ng/ml (approximately 1 pM) both in buffer and 1% human serum and can be stored and regenerated for repeated use.
Keywords: financování organizované; biosenzitivní techniky; Equipment Design; Immunoassay; virus Epsteinův-Barrové; Financing, Organized; Epstein-Barr Virus Nuclear Antigens; virus Epsteinův-Barrové - jaderné antigeny; design vybavení; analýza selhání vybavení; imunoanalýza; Antibodies; Herpesvirus 4, Human; protilátky; Equipment Failure Analysis; Biosensing Techniques